Programa de fertilización de los pastos Saboya (Megathyrsus maximus), Brachiaria (Brachiaria brizantha) y Maralfalfa (Pennisetum sp). - Mera Romero, Jheferson Adrián (2022)
At the "Mera" farm in the Palo Blanco compound. Ramón Campaña Parish, Pangua canton, Cotopaxi province, a Fertilization Program for Savoy (Megathyrsus maximus), Brachiaria (Brachiaria brizantha) and Maralfalfa (Pennisetum sp) pastures was evaluated. In the investigation, two treatments were evaluated that consisted of pasture with fertilization and grass without fertilization, for which a soil analysis was carried out at the beginning to know the state of the macro and micronutrients of the soil, in addition to a foliar analysis for each grass under study, the variables evaluated were plant height (cm) and forage production (kg/DM/ha). The best treatment was for Maralfalfa with and without fertilization, which presented the best results for plant height in the three cutting ages S/F 39.20 cm (30 days), 86.80 cm (45 days) and 98.40 cm (60 days); C/F 45.80 cm (30 days), 94.50 cm (45 days) and 102.70 cm (60 days). While forage production was for the Maralfalfa treatment with fertilization 3529.41 kg/DM/ha (30 days), 3348.42 kg/DM/ha (45 days) and 3438.91 kg/DM7ha (60 days). The foliar chemical composition reported that the nitrogen levels for the three grasses under study during and until the end of the investigation were excessive. The cost analysis allowed us to know that the fertilization of the pastures turns out to be accessible for the pocket of the agricultural producer.